Penerapan Zero Waste dalam Desain Mini Dress : Pemanfaatan Sisa Kain Sebagai Aksen Estetis. - manalu, mora (Imajinasi: Jurnal Seni, 2025)
The fashion industry is one of the largest contributors to textile waste globally. One sustainable design approach that has emerged is zero waste fashion design, a strategy that minimizes waste from the initial design phase. This study aims to implement the zero waste concept in mini dress design by utilizing fabric scraps aesthetic accents. The method used is the Double Diamond Design Process, consisting of four phases: discover, define, develop, and deliver. The results show that fabric scraps can be creatively integrated into fashion design without compromising aesthetic value. The resulting mini dress design are not only efficient in material usage but also visually appealing and aligned with sustainability principles.